ЭКОНОМИЧЕСКАЯ ЭФФЕКТИВНОСТЬ ВНЕДРЕНИЯ УСОВЕРШЕННЫХ РЕЖИМОВ РАБОТЫ ОБЪЕКТОВ ДЖИЗАКСКАЯ ГОЛОВНАЯ НАСОСНАЯ СТАНЦИЯ - Эсонтурдиев, М.Н.; Жумамуратов, Д.К. (SCIENCE and SOCIETY, 2022)
The article is devoted to determining the economic efficiency of introducing improved modes of operation of the JHPS facilities. The article presents the improvement of water supply through the machine water lifting system based on the use of modern computers, algorithms, databases and software modules when introducing a methodology for calculating water supply modes in machine water lifting systems for irrigation.